Micro needling - Facts and Fictions - Bahuguna, Amit (Asian Journal of Medical Sciences, 2013)
On 24th June 2013, the author's name was changed from Bahuga to Bahuguna. Two sentences were added to the section 'Tall Claims' on p.3. The corrected PDF is available by clicking on the link below. Micro needling or what is more commonly known as the derma-rolling is a new minimally-invasive avatar of an age old procedure. Micro needling has recently attained popularity as it is cheap, effective and can be used safely with minimal training. The basic principle is to create a controlled injury, thereby inducing the body to respond by producing more collagen in the treated area. Microneedling can be combined with other acne scar treatments for better results. Although it may not do justice to all the indications claimed by a plethora of manufacturers, if used judiciously it can prove to be a wonderful addition to the armamentarium of a dermatologist. DOI: http://dx.doi.org/10.3126/ajms.v4i3.5392 Asian Journal of Medical Sciences 4(2013) 1-4